Mapping the landscape of WCO biolubricant studies: A Comprehensive bibliometric review with vosviewer - Ilmi, Ilmi; Suherman, Suherman; Frida, Erna; Binti Mohd Zulkifli, Nurin Wahidah; Jufrizal, Jufrizal (Mechanical Engineering for Society and Industry, 2024)
This study explores the growing field of biolubricants as sustainable alternatives to petroleum-based lubricants. This paper highlights the gap in the current literature regarding biolubricants from Waste Cooking Oil (WCO) using a mixed-methods approach of bibliometric analysis and systematic literature review (SLR). A bibliometric analysis was conducted using data from the Scopus database, covering 650 publications from 2000 to 2024. Furthermore, a systematic literature review provides a comprehensive analysis of the methods used for synthesizing biolubricants from WCO, particularly evaluating the types of catalysts and methods employed that influence the physicochemical properties. The findings show a significant increase in research activity from 2018 to 2022, with Malaysia and India leading in this area. Key research trends identified include catalysts, oxidation stability, and transesterification processes. Optimal conditions for biolubricant production from WCO were achieved using an Amberlyst catalyst at 81°C, yielding a 99% conversion rate. These results highlight the potential of WCO-derived biolubricants to support more sustainable industrial applications. This study is the first to combine bibliometric analysis and systematic literature review methods to provide a comprehensive overview of research on WCO-based biolubricant production. Through a systematic review of existing studies, this research provides a useful resource for industry professionals and renewable energy policymakers in their efforts.